1974
DOI: 10.1073/pnas.71.9.3400
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin Endoperoxides. Novel Transformations of Arachidonic Acid in Human Platelets

Abstract: Arachidonic acid incubated with human platelets was converted into three compounds, 12L-hydroxy-5,8,10,14-eicosatetraenoic acid, 12L-hydroxy-5,8,-10-beptadecatrienoic acid, and the hemiacetal derivative of 8-(1-hydroxy-3-oxopropyl)-9,12L-dihydroxy-5,10-heptadecadienoic acid. The formation of the two latter compounds from arachidonic acid proceeded by pathways involving the enzyme, fatty acid cyclo-oxygenase, in the initial step and with the prostaglandin endoperoxide, PGG2, as an intermediate. The first mentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
362
0
2

Year Published

1977
1977
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,207 publications
(382 citation statements)
references
References 21 publications
18
362
0
2
Order By: Relevance
“…Its molecular formula was deduced as C 27 The individual signals in the NMR spectrum of the inhibitory compound were compatible with those of eriocitrin, as reported by Miyake et al 22 In addition, Kawai et al 23 reported that eriocitrin existed but neoeriocitrin was not detectable in Lumie fruit. From these results the inhibitory compound was identified as eriocitrin (Fig.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Its molecular formula was deduced as C 27 The individual signals in the NMR spectrum of the inhibitory compound were compatible with those of eriocitrin, as reported by Miyake et al 22 In addition, Kawai et al 23 reported that eriocitrin existed but neoeriocitrin was not detectable in Lumie fruit. From these results the inhibitory compound was identified as eriocitrin (Fig.…”
Section: Resultsmentioning
confidence: 56%
“…If one enzyme is stimulated by a selective inhibitor such as indomethacin, enhanced production of the metabolite by the other enzyme is observed. 27 Eriocitrin inhibited both 12-LOX (IC 50 22.3 µmol L −1 ) and 5-LOX (IC 50 29.1 µmol L −1 ) activities at nearly the same rate (Figs 3 and 4). Eriocitrin is converted to eriodictyol and 3,4-dihydroxyhydrocinnamic acid (3,4-DHCA) by intestinal bacteria, and conjugated forms of eriodictyol, homoeriodictyol and hesperetin, and free 3,4-DHCA were detected in rat plasma.…”
Section: Resultsmentioning
confidence: 92%
“…28-29. The fractions containing 12-HETE were pooled; an aliquot was evaporated, derivatized, and its 12-HETE structure confirmed by gas chromatography/ mass spectrometry (Hamberg and Samuels son, 1974). The 12-HETE was stored in methanol until used.…”
Section: Methodsmentioning
confidence: 99%
“…Arachidonic acid is now known to be converted by cyclo-oxygenase of the PG synthetase system to the PG endo peroxides PGG2 and PGH2 (10,11,12), precursors of PGE2 and PGF2a. The endoperoxides have contractile activity on the rat stomach fundus (13,14).…”
Section: Discussionmentioning
confidence: 99%